Consumerism: Global Vs Indian Perspectives - Dhyani, Atul (Indian Journal of Marketing, 2005)
Consumerism is a phenomenon that has managed to stay in the limelight in many industrialized nations that recently went through an economic crisis. Although consumerism has been on the scene for many decades in one form or another, the term consumerism appears to be uniquely associated with the past decade. Vance Packard one of the earliest adopters of the term, linked consumerism with strategies for persuading consumers to quickly expand their needs and wants by making them "Voracious Compulsive (and wasteful).